Extraversion Personality and Marital Satisfaction on Infidelity Tendency - Novita, Dini; Noviekayati, IGAA; Santi, Dyan Evita (Kirana Publisher (KNPub), 2025)
Marital dissatisfaction due to poor communication and conflict, as well as extraversion personality, are themain factors for infidelity tendencies. This study aims to explore the relationship between extraversionpersonality and marital satisfaction on infidelity tendencies in early adult individuals. A quantitativeapproach was used with multiple linear regression analysis method. The research sample amounted to 270early adult individuals aged 18-40 years old who were married and working, who were selected using nonprobability sampling techniques. Data were collected through questionnaires measuring extraversionpersonality, marital satisfaction, and infidelity tendencies. The results of the analysis showed thatextraversion personality had a significant positive influence on infidelity tendency (regression coefficientof 0.627, p = 0.000). In contrast, marital satisfaction did not show a significant influence on the tendency(regression coefficient -0.163, p = 0.328). Overall, the regression model was able to explain 18.3% of thevariation in infidelity tendency, while 81.7% was influenced by other factors outside of this study.